Fatores indutores e supressores da eritropoiese em caninos doentes renais crônicos - Hermeto, Larissa Correa [UNESP] (2014)
The articular cartilage is a tissue that has limited capacity for repair after an acute injury, and the efficacy of current treatments usually results in relief of symptoms, and not in regeneration of damaged tissue. Focusing on this issue, the aim of this work was to evaluate the effect of therapy with autologous mesenchymal stem cells (MSC) in the regeneration of rabbits articular cartilage submitted to experimental knee osteoarthritis. Twenty four adult New Zealand White rabbits were randomly divided into four groups: GC (control group); GPRP (platelet rich plasma group); GCTM (undifferentiated autologous mesenchymal stem cells group); GCTMdif (chondrocyte differentiated autologous mesenchymal stem cells group). All animals were osteoarthritis-induced by application of collagenase solution, and four weeks after induction, they received the specific treatments to each group. After sixty days of therapy, the animals were sacrificed and articular surfaces were submitted to macroscopic and histomorphological evaluations. At the same time were performed adipogenic, chondrogenic and osteogenic differentiation of MSC, characterizations through cytometric analysis, and evaluation of cytogenetic damage by the Comet Assay. The macroscopic and histomorphological examinations revealed a better repair tissue in the groups treated with MSC. Cytometric analyzes showed positive results for MSC immunostaining, and differentiation showed that MSC were able to differentiate into adipocytes, chondrocytes and osteoblasts. Through the Comet Assay, it was noticeable that the cytogenetic damage increased after the second passage of the MSC. It was concluded that there are beneficial effects of the combination of MSC derived from adipose tissue and platelet-rich plasma in the regeneration of articular cartilage in knees of rabbits undergoing experimental osteoarthritis, and there is no difference when MSC are used undifferentiated or differentiated into ...